Information System Audit using COBIT 2019 on Multi Finance Company - Handono Warih; Markus Adrian; Jarot S Suroso (Poltanesa, 2025)
This research paper explores the extension of COBIT 2019 into a decentralized governance framework, specifically tailored for multi-finance companies in the fintech industry. The fintech sector faces rapid technological advancements, dynamic regulatory environments, and scaling cybersecurity threats; hence, conventional governance models often do not have the flexibility and scalability to cope with these challenges effectively. It addresses these lapses by proposing a framework for governance incorporating the use of decentralized autonomous organizations, blockchain technology for transparency, and artificial intelligence for predictive risk management. The model shall be endowed with smart contracts that guarantee enforcement of compliance in an automated manner, blockchain maintenance of an unalterable audit trail, and the use of AI in finding and mitigating emerging risks in real time. These innovations are also in tune with critical COBOT 2019 domains such as MEA02 (Auditability), APO12 for Risk Management, and DSS05 for Security Services, giving them an all-encompassing and adaptive governance approach. The testing of the proposed model demonstrates significant improvement in operational resilience, regulatory compliance, and stakeholder confidence, especially within high stakes fintech environments. These findings show that incorporating emergent technologies into COBIT 2019 provides added value in governance practices and positions a scalable and future-oriented solution to help navigate the complexities of the fintech sector. This research has contributed to the development of IT governance by showing how a decentralized and technology-integrated framework can transform governance practices in ensuring agility and security within multi-finance operations.